SIMPLIFIKASI LIST ANDROID DENGAN PENGGUNAAN HASHMAP - Argo Wibowo (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2017)
In many ways android programming that can be used to achieve an outcome. One of them is to make a list. In making the list are many methods that can be used, among other things create a model, or create their own adapter. In the paper that I made this time will be discussed making a list by using hashmap. Hashmap is an abstract form of a key and value, of the key and value are provided can be matched in a list.Metode to be compared is to use the model. The result is a list that is similar, but with the use of the code more minimalist and lighter in memory usage. Hashmap the use of more flexible, because it does not need to create a model and a new class, or a new adapter.